Teachers and Students Language Politeness in English Learning at ThinkerBee Learning Center - Satyawati, Made Sri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2024)
This study discusses the principles of language politeness, as well as violations of the principles of language politeness used by teachers and students in learning English at ThinkerBee Learning Center, using a qualitative descriptive approach. The theories used in this study are the theory of the principles of politeness by Leech. The study results show that the principles of politeness in language are also used by teachers and students when learning English in the classroom. The principles of language politeness include the tact maxim 27%, the generosity maxim 18%, the approbation maxim 18%, the modesty maxim 9%, the agreement maxim 18%, and the sympathy maxim 9%. Second, this study shows violations of the principles of language politeness expressed by teachers and students during the learning process, namely violations of the tact maxim 14%, violations of the generosity maxim 28%, violations of the approbation maxim 28%, violations of the modesty maxim 14%, violations of the agreement maxim 0%, and violations of the sympathy maxim 14%.